THE ESTABLISHMENT OF COTTON AUTHORITY IN THE UZBEKISTAN SSR AND ITS CONSEQUENCES (American Journal of Pedagogical and Educational Research, 2024)
After the end of the Second World War, great changes took place in agriculture in Uzbekistan. During the war, the economy, especially the agricultural sector, suffered serious losses. Due to the war, able-bodied men went to the front, machinery was drawn to the needs of the front, and agricultural processes were derailed. In such a difficult situation, the Soviet government was forced to implement major economic and administrative measures aimed at restoring agriculture. At first, special attention was paid to the cultivation of cotton, because cotton was of strategic importance for the Union. Therefore, a cotton monopoly was established in Uzbekistan, and this situation had a serious impact on the republic not only economically, but also socially.